Metal micro-detectors: development of “transparent” position sensitive detector for beam diagnostics - O. Fedorovich, O. Kovalchuk, V. Pugatch, O. Okhrimenko, D. Storozhyk, V. Kyva (Вопросы атомной науки и техники, 2012)
Metal Micro-strip Detector (MMD) represents a novel position sensitive detector for wide range of applications. The main advantages of MMD are low thickness, high radiation resistance and high spatial resolution. MMD production technology includes some stages: micro-strip layout made by photo-lithography on silicon wafer, plasma-chemistry etching of the silicon wafer in the operating window, micro-cabling connection to the readout electronics and DAQ. Commercially available read-out systems (VA_SCM3 microchip preamplifier, Time Pix readout chip, Gotthard, X-DAS) have been studied for use with MMD. Characterization studies of the MMD are presented in details. Металлический микростриповый детектор (ММД) представляет собой новый позиционно- чувствительный детектор для широкого спектра применений. Основные преимущества ММД: малая толщина, высокая радиационная стойкость, высокое пространственное разрешение. Технология производства ММД включает в себя несколько этапов: микростриповая структура создается при помощи фотолитографии на кремниевой пластине, плазмо-химическое травление кремниевой пластины в рабочем окне, подключение микро-кабелем к считывающей электронике. Коммерчески доступные системы считывания и обработки данных (VA_SCM3, TimePix, Gotthard, X-DAS) были изучены для использования с ММД. Представлены результаты исследований MMD на пучках разных частиц. Металевий мікростріповий детектор (ММД) являє собою новий позиційно-чутливий детектор для широкого спектру застосувань. Основні переваги ММД: мала товщина, висока радіаційна стійкість, висока просторова роздільна здатність. Технологія виробництва ММД включає в себе кілька етапів: мікростріпова структура створюється за допомогою фотолітографії на кремнієвій пластині, плазмо-хімічне травлення кремнієвої пластини в робочому вікні, підключення мікро-кабелем до зчитуючої електроніки. Комерційно доступні системи зчитування й обробки даних (VA_SCM3, TimePix, Gotthard, X-DAS) були вивчені для використання з ММД. Представлено результати дослідження MMD на пучках різних частинок.